Clinical drug therapy - Frandsen, Geralyn (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Rev. ed. of: Clinical drug therapy / Anne Collins Abrams. 9th ed. c2009.; Includes bibliographical references and index.; Contents note continued: